2015
DOI: 10.1371/journal.pntd.0003640
|View full text |Cite|
|
Sign up to set email alerts
|

Proteomic Analysis of Urine Exosomes Reveals Renal Tubule Response to Leptospiral Colonization in Experimentally Infected Rats

Abstract: BackgroundInfectious Leptospira colonize the kidneys of reservoir (e.g. rats) and accidental hosts such as humans. The renal response to persistent leptospiral colonization, as measured by urinary protein biosignatures, has not been systematically studied. Urinary exosomes--bioactive membrane-bound nanovesicles--contain cell-state specific cargo that additively reflect formation all along the nephron. We hypothesized that Leptospira-infection will alter the content of urine exosomes, and further, that these Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…The suppressive effect of PEGylation might be considered a new benefit for using PEGylated liposomes in treating tumors, because it has been reported that exosomes play a controversial role in tumor progress by stimulating/suppressing the immune system. 2,4) Therefore, PEGylated liposomes may subside the bimodal role of exosomes, particularly in tumor metastasis. These observations suggest that our approach may be a new strategy to stimulate/inhibit the secretion of exosomes derived from cancer cells if the physicochemical properties of liposomes can be correctly manipulated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The suppressive effect of PEGylation might be considered a new benefit for using PEGylated liposomes in treating tumors, because it has been reported that exosomes play a controversial role in tumor progress by stimulating/suppressing the immune system. 2,4) Therefore, PEGylated liposomes may subside the bimodal role of exosomes, particularly in tumor metastasis. These observations suggest that our approach may be a new strategy to stimulate/inhibit the secretion of exosomes derived from cancer cells if the physicochemical properties of liposomes can be correctly manipulated.…”
Section: Discussionmentioning
confidence: 99%
“…45) Recently, many studies have indicated that exosomes have specialized functions and play a key role in processes such as intercellular signaling and waste management. 2) Consequently, there is growing interest in the clinical applications of exosomes. In the present study, it was shown that liposomes have the ability to upregulate and/or downregulate exosome secretion in response to the surface modification of liposomes.…”
Section: Confocal Laser Scanning Microscopy For Tracking Exosome Inmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of proper study design and normative controls it is impossible to partition biological variation from technical variation. It has thus been showed that demographic variables such as age, gender, and ethnicity can affect EV signatures [91][92][93] ; yet control groups over age, gender, and ethnicity common to other clinical research is largely lacking in EVtargeted studies 24,92 . Alternatively, pooled healthy subject samples can be used as a control 94 .…”
Section: Clinical Biological and Analytical Challenges Of Evs As Bimentioning
confidence: 99%